THE ROLE OF HOMOCYSTEINE, VITAMIN B12, AND FOLIC ACID LEVELS IN BLOOD SERUM IN ROSACEA (International Conference on Economics, Finance, Banking and Management, 2025)
Rosacea is a chronic inflammatory skin disease characterized by recurrent redness, erythema, papules, telangiectasias, edema, pustules, or a combination of these symptoms. Genetic factors, immune dysregulation, microorganisms, chronic inflammation, increased vascular reactivity, and other environmental factors are believed to play a role in the development of rosacea. Homocysteine is a sulfur-containing amino acid formed as a result of methionine metabolism. Hyperhomocysteinemia is associated with various systemic diseases, including cardiovascular, cerebrovascular and neuropsychiatric diseases.